Characterizing THz Coherent Synchrotron Radiation at Femtosecond Linear Accelerator - 林栩凌 张建兵 卢裕 雒峰 陆善良 俞铁民 戴志敏 (Chinese physics letters, 2009)
The generation and observation of coherent THz synchrotron radiation from femtosecond electron bunches in the Shanghai Institute of Applied Physics femtosecond accelerator device is reported. We describe the experiment setup and present the first result of THz radiation properties such as power and spectrum.